Profil Literasi Lingkungan dalam Mitigasi Bencana Alam Siswa di MTs Nahdlatul Ulama Mranggen Kabupaten Demak - Nur Hidayah; Muhammad Syaipul Hayat (Jurnal Kualita Pendidikan, 2022)
This study aims to describe the environmental literacy profile of students at MTs Nahdlatul Ulama Mranggen. This study uses a quantitative descriptive method. The research technique is a survey with an instrument in the form of a questionnaire. The subjects of this study were students at MTs Nahdlatul Ulama Mranggen. The location of this research was at MTs Nahdlatul Ulama Mranggen, Demak Regency, for the academic year 2021-2022. The results of the study from a sample of 53 students showed that students' ecological knowledge was included in the sufficient criteria, namely 48.3%, The environmental literacy of students in general is in good criteria, namely 68.61%. From this research, it is necessary to provide environmental literacy to students. It is hoped that this research can improve environmental literacy in flood disaster mitigation for students at MTs. Nahdlatul Ulama Mranggen.